Investigation of the Mechanical Properties of Repurposed-Net-Bag Reinforced Plastic (MIST International Journal of Science and Technology, 2025)
This study investigates the potential of recycling grocery net bags for reinforcing epoxy matrix composites, leveraging their favorable strength-to-weight ratio and offering a cost reduction and non-biodegradable waste reduction method. A composite material was made by combining 90 layers of fiber mesh with Lapox Metalam System B epoxy and hardener. The primary objective was to explore major mechanical properties, including ultimate tensile strength, yield strength, flexural strength, and impact strength. The ASTM-specified standards were maintained for the fabrication and testing of the specimen, utilizing a universal testing machine (UTM) and a pendulum impact tester. Test results show that elastic modulus of the composite ranges from 0.72 to 0.88 GPa and shear modulus ranges from 1.73 to 2.26 GPa. Also, the impact tests show an average impact strength of 66.27 kJ/m2.MIJST, Vol. 13, June 2025 : 59-64DOI: https://doi.org/10.47981/j.mijst.13(01)2025.488(59-64)